Strategi Program Tahfidz Intensif Dalam Meningkatkan Kualitas Hafalan dan Mencetak Generasi Qur’ani - Nur Kholida; Rizki Akmalia (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to analyze the strategies of the intensive Qur’an memorization program, the supporting factors contributing to its success, and its impact on students’ memorization quality and character development at Maskanul Huffadz Medan. The study employed a qualitative approach using a case study method. Data were collected through observation, in-depth interviews, and documentation, and were analyzed descriptively and analytically. The findings indicate that the intensive Qur’an memorization program is implemented through the halaqah system, the sima’i method, tiered memorization evaluations, the study of classical Islamic texts (kitab turats), and the development of an Arabic-speaking and Qur’anic learning environment. The program’s success is supported by the quality and dedication of the female Qur’an instructors (musyrifah), rigorous student selection, an active alumni network, and waqf-based financial management. The program has demonstrated a positive impact on memorization quality, as reflected in the increase in memorization retention from 80% in 2023 to 95% in 2025 and examination scores from 83 to 90. The program also contributes to students’ character development, particularly in patience, discipline, steadfastness, responsibility, reliance on God (tawakkul), and gratitude.